Improve IoT-Based Charging Management System for Electric Vehicles Considering Solar Energy Availability - Azizah, Farah; Syafii, Syafii (Andalas Journal of Electrical and Electronic Engineering Technology, 2025)
The decreasing availability of fossil fuels, coupled with escalating environmental concerns, has significantly propelled research and development efforts in renewable energy-based electric transportation systems. The emission of carbon dioxide resulting from the combustion of fossil fuels has prompted the formulation of research policies on electric vehicles (EVs) worldwide, including in Indonesia, where there is a notable increase in EV adoption and a growing demand for enhanced charging infrastructure. Utilizing solar power to charge electric vehicles can substantially decrease carbon emissions when compared to conventional charging methods that draw power from the utility grid. This research endeavors to design, develop, and implement a comprehensive grid-integrated solar-powered EV charging management system that leverages Internet of Things (IoT) technology, with a Raspberry Pi serving as the central control unit. The proposed system will incorporate a pyranometer sensor to accurately measure solar radiation levels and include a sensor to continuously monitor the battery's charging status, specifically the State of Charge (SoC). Through this integrated approach, it is anticipated that the efficiency of EV charging processes can be significantly enhanced, thereby supporting the advancement of sustainable and clean energy infrastructure. Additionally, the implementation of this system aims to contribute to reducing carbon emissions in Indonesia, aligning with national and global environmental objectives.